Elinor Ostrom's legacy and her influence in different fields - Rebatta Nieto, Javier Luis (2025)
Elinor Ostrom, winner of the Nobel Prize in Economics in 2009, left an invaluable legacy to the world through her proposal in Governing the commons (1990). Although there are more recognitions and applications, this literature review will show that there are also comments adverse to Ostrom's proposal, such as those presented by Verrax (2019), on the criticism of Hardin for The Tragedy of Commons (1968), and Lapniewska (2016), which is supported by Revollo-Fernández et al. (2016) regarding the importance of gender and its absence in Ostrom's work. Despite criticism, Ostrom's legacy is presented in many fields such as sustainability, complementary currency systems, blockchain technologies, international business, economic development, innovation systems, social entrepreneurship, macromarketing, ethical research, and in various countries around the world. world. Additionally, Ostrom's framework served as a basis for the creation of new approaches and definitions such as goods created under common property (CPA) regimes and in collective action, cooperative extension systems, communion, and polycentric governance, among others. Ostrom's legacy continues to exist and provides a framework for further developments.